IMPLIKATUR PERCAKAPAN PADA FILM MIRACLE IN CELL NO. 7 KARYA HANUNG BRAMANTYO - Wanti Wanti; Akhyaruddin Akhyaruddin; Arum Gati Ningsih (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2024)
This research aims to describe the pragmatic implications contained in the film Miracle in Cell No. 7 by Hanung Bramantyo. The method used in this research is descriptive with a qualitative approach. The data source for this research is the film Miracle in Cell No. 7 by Hanung Bramantyo. The data analysis used descriptive analysis. The results of this study are 22 conversational data points containing conversational implications in the film Miracle in Cell No. 7 by Hanung Bramantyo, namely pragmatic implications of ordering, teaching, refusing, requesting, reminding, and informing facts. The results of this study can be used as a reference source for how to speak well in everyday life.